2020
DOI: 10.3233/isu-200081
|View full text |Cite
|
Sign up to set email alerts
|

Will improvements in health journalism improve health literacy?

Abstract: Today’s health care journalists work in a very different environment than those of yesterday. The demand for stories and broadcasts has grown exponentially, and the resources available have shrunk dramatically. While it may therefore be difficult to see how improvements in health care journalism are possible, let alone a way to improve health care literacy, there is an important connection that, if illuminated, could help both fields. To understand the literature on the quality of health care journalism, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Van Antwerpen et al (2022) found that constructive journalism ‘could assist in balancing informativeness and public mental health throughout the pandemic’ (p. 506). Furthermore, constructive journalism can potentially contribute to addressing the widely accepted challenges of disengagement and misinformation in health journalism (Deprez and Van Leuven, 2018; Oransky, 2020), which have been highlighted during the pandemic. A 2020 study by Karen McIntyre measured audience's positive emotions before and after consuming constructive journalism and found that they were more likely ‘than those who did not to feel positive while consuming traditional news’ (2020: 37), suggesting that consuming constructive journalism also impacts audience's emotions when consuming non-constructive journalism.…”
Section: Constructive Journalismmentioning
confidence: 99%
“…Van Antwerpen et al (2022) found that constructive journalism ‘could assist in balancing informativeness and public mental health throughout the pandemic’ (p. 506). Furthermore, constructive journalism can potentially contribute to addressing the widely accepted challenges of disengagement and misinformation in health journalism (Deprez and Van Leuven, 2018; Oransky, 2020), which have been highlighted during the pandemic. A 2020 study by Karen McIntyre measured audience's positive emotions before and after consuming constructive journalism and found that they were more likely ‘than those who did not to feel positive while consuming traditional news’ (2020: 37), suggesting that consuming constructive journalism also impacts audience's emotions when consuming non-constructive journalism.…”
Section: Constructive Journalismmentioning
confidence: 99%